(untitled) (Indian Journal of Veterinary Pathology, 2026)
The West Nile virus (WNV), belonging to Flaviviridae, is an RNA arbovirus and a member of the Japanese encephalitis virus serocomplex, and has materialized as a major growing health risk. Because of its swift geographic expansion and development of severe diseases, a small proportion of infected cases progress to neuroinvasive disease, tied to high fatality rates, mainly in geriatric and immunocompromised populations. The enzootic transmission of WNV occurs between avian hosts and Culicine mosquitoes, with humans and various mammals functioning as accidental terminal hosts. Molecular epidemiology has identified at least seven genetic lineages, with lineages 1, 2 and 5 responsible for human disease, and considerable phylogenetic diversity influenced by migratory bird dispersal. Acute flaccid paralysis, meningitis, encephalitis, fever, and long-term neurologic sequelae are among the clinical symptoms. Diagnosis relies on serological detection of WNV-specific IgM and confirmatory neutralization assays, though cross-reactivity with related flaviviruses complicates interpretation. Currently, no licensed human vaccines or specific antiviral therapies exist, and management remains supportive. Preventive strategies focus on vector control, blood donor screening, and personal protective measures. Advances in molecular virology, ecological surveillance, and vaccine development are improving understanding of viral transmission and pathogenesis. However, knowledge gaps remain regarding vector competence, host susceptibility, and predictive modelling of outbreaks. A multidisciplinary approach integrating genomic, ecological, and clinical data is essential to guide effective prevention, therapeutic innovation, and global preparedness against WNV.